2003
DOI: 10.1007/s10038-003-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypercholesterolemia in Morocco: first report of mutations in the LDL receptor gene

Abstract: Familial hypercholesterolemia (FH) is a genetic disorder mainly caused by defects in the low-density lipoprotein receptor (LDLR) gene, although it can also be due to alterations in the gene encoding apolipoprotein B (familial defective apoB or FDB) or in other unidentified genes. In Morocco, the molecular basis of FH is unknown. To obtain information on this issue, 27 patients with FH from eight unrelated families were analyzed by screening the LDLR (PCR-SSCP and Southern blot) and apoB genes (PCR and restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…T-box proteins are an evolutionary conserved family of transcription factors ( 11 ) that exhibits a lineage-specific role during embryogenesis by enhancing and/or repressing the transcriptional expression of a network of genes ( 12 ). TBX family members are sub-classified according to their sequence homology and pattern of expression ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…T-box proteins are an evolutionary conserved family of transcription factors ( 11 ) that exhibits a lineage-specific role during embryogenesis by enhancing and/or repressing the transcriptional expression of a network of genes ( 12 ). TBX family members are sub-classified according to their sequence homology and pattern of expression ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the correlation between genotype and phenotype is clear in homozygotes, it is less evident in heterozygotes for FH. These results show the improved diagnostic precision obtained by introducing genetic diagnosis in FH families with identified mutation (Civeira 2004), even when the mutation spectrum of the LDLR gene in Moroccan population seems to be heterogeneous (El Messal et al 2003Chater et al 2006). Finally, further studies are needed to elucidate the molecular basis of the HALP observed in the studied family and the role of the reduced HDL-C levels in the development of atherosclerosis in a FH context.…”
Section: Discussionmentioning
confidence: 81%
“…LDLR gene: We analysed LDLR gene by Southern blot (El Messal et al 2003) and PCR-SSCP. For SSCP analysis, PCR products were added to 95% formamide buffer, denatured at 95 • C for 5 min, immediately chilled on ice and electrophoresed at 1050 V, at 25 • C or 15 • C in a MDE gel with or without 5% glycerol, respectively, in 0.6 × TBE buffer for 15 h, on an automated DNA sequencer equipped with a water jacket (ALF-Express TM , Pharmacia Biotech).…”
Section: Subjectsmentioning
confidence: 99%
“…2004; Salazar et al . 2002; El Messal et al . 2003) have reported the detection of the 370T allele in FH patients, and have included these subjects in their mutation detection rate analysis, or in genotype‐phenotype analysis (Wang et al .…”
Section: Discussionmentioning
confidence: 99%